Analysis of Drainage Channel Construction Work Time Using the Trade Cost Trade Off (TCTO) Acceleration Method in Ponorogo Regency - Bela Prayogo; Laksono Djoko Nugroho; Esti Wulandari (Publica Scientific Solution, 2026)
Drainage infrastructure development plays a crucial role in supporting urban environmental quality and preventing waterlogging and flooding. However, construction projects often experience delays that hinder infrastructure performance. In the drainage channel construction project on Letjend Suprapto Street and Menur Street, Ponorogo Regency, a progress deviation of ?30.26% occurred in the eighth week, indicating the need for an effective acceleration strategy. This study aims to analyze the effect of applying the Trade-Off Cost–Time (TCTO) method on project time acceleration and cost changes. This research employed a quantitative approach using network planning analysis with Microsoft Project to identify the critical path, followed by crashing analysis through additional work shifts and cost slope calculations using the TCTO method. The findings indicate that the project duration can be reduced from 65 days to 60 days by implementing a two-shift work system. This acceleration resulted in an increase in direct costs from IDR 2,390,347,251.56 to IDR 2,411,296,170.48. The TCTO method is proven effective in accelerating project duration with manageable additional costs, making it a viable solution for overcoming delays in drainage construction projects.